Analisis Faktor Risiko Kelelahan Kerja pada Kurir PT Tiki Jalur Ekakurir (JNE) di Wilayah Kecamatan Pondok Gede Kota Bekasi Tahun 2022 - Febriana, Dinda Arsyah; Susilowati, Indri Hapsari Hapsari (National Journal of Occupational Health and Safety, 2023)
This study aims to describe the fatigue risk factors experienced by PT JNE couriers in the Pondok Gede District, Bekasi City in 2022. The study was conducted on 31 couriers operating in the Pondok Gede area and its surroundings in May – June 2022. This study uses a study cross-sectional with quantitative methods. The dependent variable of this study is work fatigue, and the independent variable is work-related risk factors (work shift, work duration, rest time), non-work risk factors (service period, commuting time, and satisfaction with the incentive and reward system), and individual factors (age, nutritional status, sleep quality, sleep quantity, fear of Covid-19, and breakfast habits). The results showed that 51,6% (16 people) experienced moderate fatigue, 35,5% (11 people) experienced mild fatigue, and 12,9% (4 people) did not. Moderate fatigue tends to be experienced by excessive work duration (39,3%), low workload (75%), adequate rest (45%), day shift (41,7%), working period > 5 years (47,1%), long commuting time (57,1%), satisfied with the reward system (45%), satisfied with the incentive system (47,4%), age 35 years (37,9%), sleeping less than 7 hours (53,8%), excess nutritional status (40%), and mild fear of COVID-19 (40%).